Land Relations in the Construction of Linear Facilities in Ukraine: Institutional Aspect - Sharyi, Grigoriy; Gryshko, Volodymyr; Dubіshchev, Viktor (International Journal of Engineering and Technology, 2018)
The given paper is dedicated to the determination of the possible ways to solve the problems of extractive industries and power engineering  spatial development in combination with sustainable use and protection of lands, as well as ensuring the institutionalization of various environmental, legal and economic aspects. Specific ways of improving servitude relations are determined by authors. Additionally, institutionalism is considered to be the methodological basis for the development of land relations at the state level. The current norms of land legislation in many cases do not take into account the spatial problems and production specificity with regard to the location of pipeline, energy infrastructure, oil and gas wells and production facilities associated with their operation  Temporary ways of solving issues related to the acquisition of the right of land for the needs of oil and gas industry by concluding land servitude agreements have been found.  To solve this problem and to ensure timely implementation of the state program for the extraction of natural gas and oil  is necessary to supplement the Land Code of Ukraine with a new Article 1001 on the specifics of establishing land servitudes for the placement of pipeline transport facilities, oil and gas wells.